Genetic characterization of canine astrovirus in non-diarrhea dogs and diarrhea dogs in Vietnam and Thailand reveals the presence of a unique lineage - Nguyen, Tin Van; Piewbang, Chutchai; Techangamsuwan, Somporn (Frontiers in Veterinary Science, 2023)
The role of canine astrovirus (CaAstV) in canine gastrointestinal disease (GID) is unknown. In this study, a total of 327 fecal swab (FS) samples were collected, including 113 FSs in Vietnam (46 samples from healthy dogs and 67 samples from GID dogs) and 214 FSs in Thailand (107 samples from healthy dogs and 107 samples from GID dogs). Overall, the prevalence of CaAstV in Vietnam and Thailand was 25.7% (29/113) and 8.9% (19/214), respectively. CaAstV was detected in both non-diarrhea dogs (21.7% and 7.5%) and diarrhea dogs (28.4% and 10.3%), respectively, in Vietnam and Thailand. In both countries, CaAstV was frequently detected in puppies under 6 months of age (23.3%) (p = 0.02). CaAstV-positive samples in Vietnam and Thailand were identified as co-infected with canine parvovirus, canine enteric coronavirus, canine distemper virus, and canine kobuvirus. The complete coding sequence of seven Vietnamese CaAstV and two Thai CaAstV strains were successfully characterized. Phylogenetic analyses showed that Vietnamese and Thai CaAstV strains were genetically close to each other and related to the Chinese strains. Furthermore, analysis of complete coding sequences indicated that the OR220030_G21/Thailand/2021 strain formed a unique lineage, whereas no recombination event was found in this study, suggesting that this strain might be an original lineage. In summary, this is the first study to report the presence of CaAstV in dogs with and without diarrhea in Vietnam and Thailand, and it was most often found in puppies with diarrhea. Our results highlight the importance of the CaAstV in dog populations and the need for continued surveillance of these emerging pathogens.